2022
DOI: 10.1177/23996544211063205
|View full text |Cite
|
Sign up to set email alerts
|

Who will man the rigs when we go?” transnational demographic fever dreams between Qatar and Texas

Abstract: The educational project of producing engineers in Qatar is uniquely embedded in global capitalism, particularly as a field closely tied to the development of the oil and gas industry, the military and logistics spaces across the Gulf. Over the past two decades, U.S. universities based in the region have become significant spaces where new generations of managerial engineering labor are educated. Drawing on 18 months of institutional ethnographic research, I examine Texas A&M University at Qatar’s (TAMUQ) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Over half of all offshore campus students in Dubai, for example, are enrolled in business‐related programmes (Knowledge and Human Development Authority, 2017), feeding into the city's internationally coupled service and trade economy. There are similar tendencies in the other cities, for example, the relationship between Doha's Texas A&M campus and the transnationally organized oil and gas industry (Al‐Saleh, 2022). Most university managers echoed the government administrators in their explanations of how their graduates are crucial for the international trajectory the governments have chosen for economic development: ‘We supply people who are able to think critically across the board, who are numerate and literate, and who know how the world works, and how the local and regional fit to the global’ (offshore campus manager in Doha).…”
Section: Doha Dubai and Ras Al‐khaimah As Tne Gateway Citiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Over half of all offshore campus students in Dubai, for example, are enrolled in business‐related programmes (Knowledge and Human Development Authority, 2017), feeding into the city's internationally coupled service and trade economy. There are similar tendencies in the other cities, for example, the relationship between Doha's Texas A&M campus and the transnationally organized oil and gas industry (Al‐Saleh, 2022). Most university managers echoed the government administrators in their explanations of how their graduates are crucial for the international trajectory the governments have chosen for economic development: ‘We supply people who are able to think critically across the board, who are numerate and literate, and who know how the world works, and how the local and regional fit to the global’ (offshore campus manager in Doha).…”
Section: Doha Dubai and Ras Al‐khaimah As Tne Gateway Citiesmentioning
confidence: 89%
“…Kleibert et al (2020) have identified 487 offshore campuses operating in various forms and sizes worldwide, with most campuses being exported from the industrialized global North to Southeast Asia and the West Asia and North Africa (WANA) region. So far, the phenomenon has largely attracted scholarship from managerial and education studies (Kosmützky, 2018;Wilkins & Huisman, 2012) although some geographers have started to conceptualize its wider socio-spatial implications (Al-Saleh, 2022;Koch, 2016). More research is required on how such transnationally mobile universities are entangled with the positionalities of the cities they go to.…”
Section: Converging Global Geographies Of Higher Education and Tne St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Universities further facilitated colonization and imperialism by producing knowledge and labor to render the land productive for capital accumulation-ranging from agricultural extension schools to refining methods for fossil fuel extraction and arid lands expertise (Koch, 2023;Tretter, 2020). The educational and research infrastructure developed through this colonial relationship to land's commodification allowed for U.S. universities to be uniquely positioned in the global neoliberal counter-revolution and materially shape urbanization processes (Baldwin, 2021), resource extraction (Al-Saleh, 2022;Beasley, 2018), and development practices and ideologies (Kamola, 2019).…”
Section: Political Ecologies Of the University And Landmentioning
confidence: 99%